Implementation of the Principle of Nemo Plus Juris in the Registration Process Through Electronic Systems - Nurmuhyiddin Qasim, Muhammad Thahir; Aswari, Aan; Rahim, Dinaryati (Qawanin Jurnal Ilmu Hukum, 2025)
Abstract: This research aims to detail the application of the nemo plus iuris principle in the land registration process through the electronic system at the Makassar City Land Office, as well as the implementation of land registration through the electronic system at the Makassar City Land Office. In this research, legal regulations and field realities will be detailed to answer this thesis. This research uses the empirical legal research method, with the research location at the Makassar City Land Office. Data collected through interview techniques and literature study, which were then analyzed descriptively and analytically. The research results show that the application of the nemo plus yuris principle has been well implemented, and is reinforced by the principle of prudence and strict system oversight. The application ensures that the data inputted matches the original documents at the online file verification stage, and automatic rejection occurs if there are discrepancies. In this case, the implementation of land registration through the electronic system has shown significant progress in improving the efficiency of land services to the community. Research recommendation, the Makassar City Land Office should enhance land registration through an electronic system to reduce the risk of land disputes. And strengthen cooperation with PPAT to ensure that every deed made is in accordance with the field conditions and applicable legal regulations. Keywords: Land Registration, Electronic Certificates, Nemo Plus Yuris Abstrak: Penelitian ini bertujuan untuk merinci penerapan asas nemo plus yuris dalam proses pendaftaran tanah melalui sistem elektronik, serta pelaksanaan pendaftaran tanah melalui sistem eletronik di Kantor Pertanahan Kota Makassar. Di dalam penelitian ini peraturan hukum dan kenyataan di lapangan akan di rinci dalam menjawab skripsi ini. Penelitian ini menggunakan metode penelitian hukum empiris, dengan lokasi penelitian di Kantor Pertanahan Kota Makassar. Data yang dikumpulkan melalui teknik wawancara dan studi pustaka, yang kemudian dianalisis secara deskriptif analitis. Hasil penelitian menunjukkan bahwa penerapan asas nemo plus yuris telah diterapkan dengan baik, dan diperkuat oleh prinsip kehati-hatian serta pengawasan sistem yang ketat. Aplikasi memastikan data yang diinput sesuai dengan dokumen asli pada tahapan verifikasi berkas secara online dan penolakan otomatis terjadi jika terdapat ketidaksesuaian. Dalam hal ini dalam pelaksanaan pendaftaran tanah melalui sistem elektronik telah menunjukkan kemajuan yang signifikan baik dalam meningkatkan efisiensi pelayanan pertanahan kepada masyarakat. Rekomendasi penelitian, Kantor Pertanahan Kota Makassar meningkatkan pendaftaran tanah melalui sistem elektronik untuk mengurangi resiko sengketa tanah. Dan memperkuat kerja sama dengan PPAT untuk memastikan setiap akta yang dibuat telah sesuai dengan kondisi lapangan dan aturan hukum yang berlaku. Kata Kunci: Pendaftaran Tanah, Sertipikat Elektroni, Nemo Plus Yuris